Prolonged Antibiotic Use and Reproductive Challenges in Dairy Cows: Implications for Ovarian, Uterine, and Overall Reproductive Health - Md. Emran Hossain (International Journal of Antibiotics, 2026)
The widespread use of antibiotics in dairy farming has raised concerns regarding its potential impact on reproductive performance. Prolonged antibiotic administration can disrupt endocrine regulation, alter ovarian function, impair uterine health, and compromise overall fertility in dairy cows. This review explores the multifaceted consequences of antibiotic exposure on reproductive physiology, highlighting its effects on hormonal balance, follicular dynamics, uterine microbiota, and embryo viability. Antibiotics may induce hormonal imbalances that interfere with estrous cyclicity, leading to anovulation, prolonged postpartum anestrus, and reduced conception rates. Ovarian dysfunction, characterized by impaired folliculogenesis and increased ovarian cyst formation, is another critical consequence. Additionally, prolonged antibiotic exposure alters the uterine microbiome, increasing susceptibility to endometritis and subclinical infections that hinder uterine involution and embryo implantation. The development of antimicrobial resistance in reproductive pathogens further complicates fertility management in dairy herds. Furthermore, antibiotic residues may persist in tissues, affecting fetal development and postnatal growth of offspring. Addressing these challenges requires an integrative approach, incorporating precision antibiotic use, alternative therapeutic strategies, and microbiome-targeted interventions to optimize reproductive efficiency. Future research should focus on understanding microbial-host interactions in reproductive tissues and developing sustainable solutions to minimize antibiotic-associated fertility decline in dairy cows.
Keywords: antibiotic resistance; dairy cow fertility; embryo viability; hormonal imbalance; ovarian dysfunction; reproductive health; uterine microbiota